2011
DOI: 10.1590/s0370-44672011000100002
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and chemistry of archaeological ceramic fragments from archaeological Dark Earth site in Colombian Amazon

Abstract: ResumoVários sítios arqueológicos de Terra Preta Arqueológica (TPA) encontrados na floresta Amazônica Colombiana também contêm alto conteúdo de fragmentos cerâ-micos semelhantes aqueles da Amazônia Brasileira, como mostra o sítio Quebrada Tacana. Seus fragmentos cerâmicos são amarelo a cinza, exibem matriz argilosa calcinada envolvendo fragmentos de cariapé, carvão e partículas de cinza, grãos de quartzo e micas. A matriz é composta de metacaulinita a material amorfo, quartzo, folhas de micas, clorita e sepiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 10 publications
0
9
0
2
Order By: Relevance
“…Sponges are sessile aquatic animals of the phylum Porífera that need substrates to develop and can live in association with other animals (Volkmer-Ribeiro, 1981). The use of sponge spicules in the production of ceramics has been documented in archaeological sites in the Amazon basin (Evans & Meggers, 1962;Costa et al, 2011). The fertilization of the soil of the archaeological site through anthropic action with the use of sediments from floodplain areas may also be an explanation for the occurrence of sponge spicules and diatomaceous frustules in these materials (Lima et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Sponges are sessile aquatic animals of the phylum Porífera that need substrates to develop and can live in association with other animals (Volkmer-Ribeiro, 1981). The use of sponge spicules in the production of ceramics has been documented in archaeological sites in the Amazon basin (Evans & Meggers, 1962;Costa et al, 2011). The fertilization of the soil of the archaeological site through anthropic action with the use of sediments from floodplain areas may also be an explanation for the occurrence of sponge spicules and diatomaceous frustules in these materials (Lima et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…O estudo regional realizado por Sá 2017 , 1962;COSTA et al, 2011). A fertilização do solo do sítio arqueológico pela ação antrópica com o uso de sedimentos de áreas de planície de inundação também pode ser uma explicação para a ocorrência de espículas de esponjas e frústulas de diatomáceas nestes materiais (LIMA et al, 2002).…”
Section: Discussionunclassified
“…Similar results were obtained for the Terra preta at Caxiuanã and in Pará, where the contents of total P, Ca, Zn, and Mn were much higher in comparison to surrounding soils (Kern, 1996). Some authors have worked on the chemical content of fragmented potteries found in the Terra preta in the Amazon Basin (Da Costa et al, 2011;Costa et al, 2013). Most of these studies revealed that areas with the highest density of pottery fragments coincide with the highest contents of elements such as Zn, Cu, Mn, Ba, and Sr.…”
Section: Physicochemical Properties Of Amazonian Dark Earthmentioning
confidence: 99%